2013
DOI: 10.28945/1792
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students’ Likelihood to Purchase Electronic Textbooks

Abstract: Technological advances touch multiple aspects of an individual's life. One such example is the use of information technology to provide online books. Online books have been introduced in education in the form of electronic textbooks (e-texts). The research question examined here is among those students who have purchased or used an e-text, what factors motivate their willingness or likelihood to purchase an e-text? A model and hypotheses linking the factors of usefulness, arousal, ease of use, value, and effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The perceived usefulness, convenience, compatibility, and perceived enjoyment in the combined model are suggested to be influential factors contributing to dedicated e-textbook application acceptance. More recently, Stone and Baker-Eveleth (2013b) examined the likelihood of students purchasing an electronic textbook with an extended TAM. The results indicated that an e-textbook's usefulness, ease of use, and students' arousal E-textbook adoption…”
Section: Past Studies On E-textbooksmentioning
confidence: 99%
“…The perceived usefulness, convenience, compatibility, and perceived enjoyment in the combined model are suggested to be influential factors contributing to dedicated e-textbook application acceptance. More recently, Stone and Baker-Eveleth (2013b) examined the likelihood of students purchasing an electronic textbook with an extended TAM. The results indicated that an e-textbook's usefulness, ease of use, and students' arousal E-textbook adoption…”
Section: Past Studies On E-textbooksmentioning
confidence: 99%
“…On the other hand, ease to use is one of the important factors that contributed to the motivation to purchase the e-textbook (Stone and Baker, 2013). The results in the Robert et.al (2021) study also indicated that ease of use has a significant impact on student likelihood to purchase e-textbook.…”
Section: Ease Of Usementioning
confidence: 97%
“…Technology advancement affects many aspects of an individual's life (Stone and Baker, 2013) and yet, it is vital to access all information especially among university students. Due to this, the electronic books which are also known as e-text may provide students, professors, universities, and colleges with additional tools to support process learning in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of technology cannot be denied bringing innovation that can play an essential role in education. In this case, technological advances touch various aspects of individual lives (W. Stone & Baker-Eveleth, 2013). Improving understanding and reusing these resources can be done by adopting digital technology to analyze and manage learning resources.…”
Section: Introductionmentioning
confidence: 99%